Does behavioural economics equip policy-makers with a complete (enough) picture of the human: the case of nudging - Wincewicz-Price, Agnieszka (Journal of Public Governance, 2019)
Objectives: The article offers a critical discussion of the policy of nudging and suggests so far unexplored evaluation criteria for behavioural policy experts and practitioners.Research design: A multi-disciplinary approach is taken here to fill out the thin anthropology of homo economicus – which is shown to inform the concept of nudging – with selected aspects of human agency which are commonly discussed in moral, political and economic philosophy. The aim of this paper is twofold: 1) to outline the conceptual shortcomings of the behavioural foundations of the nudge theory as it has been originally proposed by Thaler and Sunstein; 2) to suggest several non-behavioural aspects of human agency and action which extend the original concept of nudging and should be accounted for by policy-makers in their design of nudge-like behavioural interventions.Findings: It is claimed that mere inclusion of cognitive biases and irrationalities in the behavioural approach to policy does not sufficiently extend the artificial concept of the rational agent; in particular this narrow understanding of human failure misses important aspects of the rich concept of well-being.Implications: The use of nudges requires a comprehensive knowledge of the application context. In underspecified decision contexts, choice architects need to apply more care and critical reflection in order to prevent unintended or harmful consequences of nudging.Contribution: It is rare for pragmatically oriented public policy research to focus on the philosophical concepts that inform its theory and practice. This paper is a philosophical reflection on some key elements inherent in nudging. It helps better to understand the ambiguous design, potential and limitations of nudge policy.